Вы находитесь на странице: 1из 22

.

5 2013


.
,
.
.
.


,
y = f (x), a x b ( f (x) 0),
y = 0, x = a x = b
Zb
S = f (x) dx.
a

y
y = f (x)

b
.


Z
C dx = C(b a),

Zb

Zb
f (x) dx

g(x) dx f (x) g(x) a x b,

Zb

Zc
f (x) dx =

Zb
f (x) dx +

f (x) dx.
c

,
, ,
,
,
.


Zb
S=

f (x) dx
a



f (x) y g(x), a x b,
Zb
(g(x) f (x)) dx.

S=
a

y
y = g(x)

S
y = f (x)
a

f (x) g(x).
.

x = f (y ) x = g(y ), c y d,
f (y ) x g(y ):
Zd
(g(y ) f (y )) dy .

S=
c

y
d

x = f (y)

x = g(y)

c
.

Zb
S=

l(x) dx.
a

Ox , l(x)
, Ox
Ox.


,
:
V = SH = R 2 H.
0 y f (x),
a x b (f (x) 0). Ox.
.
V .
a = x0 < x1 < . . . < xn = b ,
Ox ,
,
,
xi xi1 , i = 1, . . . , n.
Vi =

n
X

yi2 (xi xi1 ).

i=1
.

Zb
f (x)2 dx.
a

Ve

Vi V Ve .
, V ,
.
Zb
V =

f (x)2 dx.

,
:
1

V = R 2 (b a), f (x) = R = const

Vf Vg , f (x) g(x)

V = V1 + V2 , .

, . Ox
, S(x)
, x.

Zb
V =

S(x) dx.
a


y = f (x), a x b. ,
,
.
.
.



l 2 = x 2 + y 2 .
,

l 2 = x 2 + (f 0 ()x)2 = 1 + f 0 ()2 x 2 .

,

L=

Zb q

1 + f 0 (x)2 dx.

,
,
x = x(t), y = y (t), t .

p
p
dl = dx 2 + dy 2 = x 0 (t)2 + y 0 (t)2 dt,

L=

Z q

x 0 (t)2 + y 0 (t)2 dt.

x = x(t), y = y (t), z = z(t), t .



q
p
dl = dx 2 + dy 2 + dz 2 = x 0 2 + y 0 2 + z 0 2 dt,

L=

Z q

x 0 (t)2 + y 0 (t)2 + y 0 (t)2 dt.


,
(..
).


Zb

S = Ha

S=

f (x) dx
a

V = R 2 H

Zb
V =

f (x)2 dx

k
p
L = 1 + k 2 (x2 x1 )


Zb q
L=
1 + f 0 (x)2 dx
a


ZT

s = vT

s=

v (t) dt
0


Zs

A = Fs

F (x) dx

A=
0


,
,

. ,
,

2
erf(x) =

Zx

et dt.

,
lim erf(x) = 1.

.
.